Socio-environmental factors and schistosomiasis hospitalizations in Minas Gerais, Brazil (2007-2017) - Mario Ribeiro Alves (Universidade do Estado de Mato Grosso, 2022)
Objective: to spatially analyze the disease in the state of Minas Gerais, Brazil, associating its transmission with possible exposure factors. Method: descriptive ecological study, based on secondary data, with statistical and spatial analysis. Collection of cases of the disease was carried out by municipality. Maps were made for spatial approach. Results: cases of the disease were analyzed accompanied by their respective MHDI, percentage of people in households with inadequate water supply and sanitation, percentage of the population in households without running water and percentage of the population in households without garbage collection. Conclusion: in order to control the disease, improvements are proposed in the basic sanitation infrastructure (sewage treatment and water supply) and public awareness through the dissemination of educational material. Even within a municipality, there are different levels of development and health, so that the data may not represent the entire reality of a municipality.